Dipana, Pachana, Agni, and Metabolism: A Synergistic Perspective on Health - Mohammed. Asif; Siva Sahithi (International Journal of Ayurveda and Pharma Research, 2025)
In Ayurveda, the concepts of Dipana (enhancing digestive fire) and Pachana (burning or metabolizing toxins) play vital roles in maintaining health and vitality. These principles resonate deeply with modern scientific understandings of metabolism, the biochemical engine that powers our body. A closer look reveals intriguing correlations between Dipana and exercise, Pachana and fasting, and their mutual connection through the concept of Agni, the Ayurvedic term for digestive and metabolic fire. This article dwells into detailed analysis of these aspects along with their actions on the body.